Current therapeutic landscape in multiple sclerosis: an evolving treatment paradigm - Cree, Bruce A C; Mares, Jan; Hartung, Hans-Peter (Current opinion in neurology, 2019)
PURPOSE OF REVIEW: To critically assess the current landscape of disease-modifying agents for multiple sclerosis (MS). Treatment algorithms will be discussed and studies for new agents in late development or recently approved are analyzed in terms of their impact on current treatment strategies. RECENT FINDINGS: A real-world study from Wales suggests that early initiation of highly effective therapy may provide more benefit that an escalation approach in relapsing MS. A study from the MSBase dataset found evidence that early treatment with highly effective therapies decreased the risk of developing secondary progressive MS. Ocrelizumab is highly efficacious in relapsing MS and in a group of patients with primary progressive MS. Another CD20 directed mAb, ofatumumab, is in phase 3. A large study examining extended interval dosing of natalizumab in an attempt to decrease the risk of developing progressive multifocal leukoencephalopathy is underway. Cladribine and alemtuzumab may work by immune reconstitution. Siponimod was recently approved by United States Federal Drug Administration for relapsing MS and active secondary progressive MS. Other S1P receptor modulators are being studied in phase 3 trials for relapsing MS. Cladribine received FDA approval as treatment for relapsing and active secondary progressive MS. Autologous hematopoetic stem-cell transplantation may be an option for treatment-refractory MS. SUMMARY: Development of disease-modifying agents in MS continues to be successful. Treatment algorithms need to take new developments into account.
Keywords: imunosupresiva; Alemtuzumab; Antibodies, Monoclonal, Humanized; roztroušená skleróza; alemtuzumab; lidé; vyvíjení léků; Immunosuppressive Agents; natalizumab; Natalizumab; humanizované monoklonální protilátky; Humans; Drug Development; Multiple Sclerosis